Localized Laryngeal Amylodosis Successful Treatment With Systemic Therapy - A Case Report - R. Amilah; H. Shahrul; Nor Eyzawiah Binti Hassan; A. B. Azreen (SCIENCEDOMAIN International, 2024)
Non-Indexed Publication